PENYELESAIAN SENGKETA PERBANKAN SYARIAH MELALUI PENGADILAN AGAMA: SUATU STUDI HUKUM NORMATIF - Ana Laela (Jurnal Geuthèë: Penelitian Multidisiplin, 2021)
Islamic banking is an economic business activity that is expected to be an alternative solution for efforts to optimize the potential of the community's economic resources, especially for Muslim communities who have long doubted the interest system in conventional banking, which can eliminate all forms of usury economic business practices, formally juridical recognition of economic principles. Sharia has been included in Law no. 3 of 2006 as an amendment to Law No. 7 of 1989, which confirms that the Court in its duties and authorities can decide Sharia Economic cases, while the issue of sharia economic disputes is relatively new and not widely known in the legal world. So the author would like to review the readiness of Religious Court judges in settlement of Sharia Economic disputes using a juridical-normative, conceptual and legal approach.